2020
DOI: 10.3390/ijerph17082760
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sleeping Patterns in Health and Academic Performance Among University Students

Abstract: Sleep problems in university students are important and have implications for health, quality of life, and academic performance. Using an ex post facto design, a total sample of 855 students (55.7% women) participated in the study. Sleep assessment was conducted using the Pittsburgh Sleep Quality Index, the Nightmare Frequency Scale, the Nightmare Proneness Scale, and the Composite Morningness Scale. Women show a higher risk [OR = 2.61] of presenting poor sleep quality (> 5 points on the PSQI) compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 64 publications
2
19
0
1
Order By: Relevance
“…Other processes could also underpin relationships between nightmare proneness, nightmare frequency, and insomnia. For instance, all three variables have been associated with an evening chronotype (Nielsen, 2010; Ong et al, 2007; Toscano-Hermoso et al, 2020). It is possible that variations in the sleep–wake cycle and associated physiological processes involving the suprachiasmatic nucleus are important in the interrelationships between nightmare proneness, insomnia, and nightmare frequency (Roenneberg et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other processes could also underpin relationships between nightmare proneness, nightmare frequency, and insomnia. For instance, all three variables have been associated with an evening chronotype (Nielsen, 2010; Ong et al, 2007; Toscano-Hermoso et al, 2020). It is possible that variations in the sleep–wake cycle and associated physiological processes involving the suprachiasmatic nucleus are important in the interrelationships between nightmare proneness, insomnia, and nightmare frequency (Roenneberg et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this approach, mediation is considered significant if zero is not included in the 95% bias-corrected confidence interval of the indirect effect (Preacher & Hayes, 2008). Given past findings of associations with gender (Schredl & Reinhard, 2011; Toscano-Hermoso et al, 2020), it was used as a covariate along with neuroticism and negative response bias in the mediation analyses. Cohen’s (1988) f 2 was used to determine effects sizes for the full models predicting each insomnia marker: .02, .15, and .35 denote small, medium, and large effects, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, a number of studies on the interaction between subjective sleep and academic achievement of university students have emerged. Ahrberg et al (2012) , Baert et al (2015) , and Toscano-Hermoso et al (2020) reported a positive relationship between sleep quality and academic scores. Gomes et al (2011) found poor sleep quality and insufficient sleep to be significantly associated with poorer academic performance.…”
Section: Introductionmentioning
confidence: 92%
“…For example, in a study by Kamimura et al (2000) [ 11 ], 61% of female college students were evening-types. Moreover, compared to their male counterparts, female students took longer to fall asleep after going to bed, had poorer quality of sleep [ 21 , 22 ], and had worse overall sleeping conditions [ 2 ]. Many studies have reported that evening-type sleep habits were related to uncomfortable psychosomatic symptoms, particularly in young women.…”
Section: Introductionmentioning
confidence: 99%